Increasing Motivation and Managing Digital Administration Using Google Drive Through in House Training for Administrative Staff of SMKN 1 Punggelan (Universitas Negeri Semarang, 2022)
The effectiveness of archives management in an organization is greatly influenced or supported by employees in the administration section, the facilities or facilities used in archive management and the availability of funds for archive maintenance and archive maintenance. SMK Negeri 1 Punggelan has administrative officers or staff whose job is to manage documents or archives which are carried out starting from the start of the archives to the depreciation of the archives but most of them are still manual. This School Action Research aims to: (1) To describe an increase in motivation to use Google Drive for digital administration through IHT activities for administrative staff at SMK Negeri 1 Punggelan and (2) To describe an increase in the ability to use Google Drive for digital administration through IHT activities for administrative staff at SMK Negeri 1 Punggelan. Research on motivation using Google Drive for digital archives that the author has done can increase motivation using Google Drive from 25% or 3 people in the very good and good category in the pre-cycle to 50% or 6 people in cycle I and 1.66% or 11 people in cycle II, as well as for the ability to use google drive for digital administration which the author has done can increase from 33.33% or 4 people in the very good and good categories in the pre-cycle to 56.